Eosinophilic esophagitis-Where are we today?, - Ferreira,Cristina Targa (2019)
Abstract Objective: The objective of this review is to provide an overview of the practical diagnostic and therapeutic approaches to eosinophilic esophagitis and to increase the visibility of the disease among pediatricians. Sources: A search of the MEDLINE, Embase, and CINAHL databases and recent consensus statements and guidelines were performed. Summary of the findings: The definition of eosinophilic esophagitis is based on symptoms and histology. It is important to rule out other diseases associated with esophageal eosinophil-predominant inflammation. It is not yet clear whether the increased prevalence is due to a real increase in incidence or a result of increased awareness of the disease. Various options for management have been used in pediatric patients, including proton pump inhibitors, dietary restriction therapies, swallowed topical steroids, and endoscopic dilations. More recently, proton pump inhibitor-responsive esophageal eosinophilia and eosinophilic esophagitis have been contemplated on the same spectrum, and proton pump inhibitors should be considered the initial step in the treatment of these patients. Conclusions: Eosinophilic esophagitis is a relatively new disease with a remarkable progression of its incidence and prevalence in the past two to three decades, and diagnostic criteria that are constantly evolving. It is important to better understand the pathogenesis of the disease, the predisposing factors, the natural history, and the categorization of varying phenotypes to develop diagnostic and therapeutic strategies that meet the clinical needs of patients.